Management of Instagram @prokompim.subang as A Communication and Information Medium to Improve the Image of the Regent of Subang Regency in the Community in 2018-2023 - Sari, Oktaviani Nurindah; Sofyan, Nur (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The management of Instagram social media has become very effective in improving the image of the Regent of Subang Regency in the eyes of the public, which previously had problems during the previous three periods of the Regent's leadership. Managing Instagram is very important to improve the image of the regent and the agency. Prokompim's Instagram is a source of information for the people of Subang Regency, providing information related to the regent's program. The existence of Instagram management makes it easier to communicate with people whose reach is quite far. This research uses a qualitative study with a post-positivist paradigm, testing the validity of the data used through source triangulation and data analysis techniques through data collection, data reduction, data presentation, and conclusion. After three years of managing Instagram, Prokompim Subang has produced effective results in repairing and enhancing the image of the Subang regent in society, as seen from the many responses and activities in the social media space. The social media management carried out by Prokompim Subang is based on leadership, social media, image, and communication media answering all of these things, for example, publications on social media related to achievements so that the public can see the performance of the current regent period, which makes Instagram now as a medium of communication with the people of Subang Regency which is applied to improve its image. In this research process, some limitations can influence the research results, namely the limited research time, the ability of respondents to answer the interview guide, and this research can answer the management of Instagram @prokompim.subang as a medium of communication and information to improve the image of the Regent of Subang Regency in the community in 2018-2023. However, this research could not answer the management of the same Instagram account in improving the image of the Subang district regent.